Building ecological citizenship awareness for a healthy Indonesia - Darto Wahidin; Rr. Nanik Setyowati (Universitas Negeri Yogyakarta, 2026)
Environmental issues are increasingly pressing globally, including in Indonesia, where pollution and environmental damage continue to rise. In this context, ecological citizenship awareness has emerged as one solution to address these challenges. This study aims to analyse the level of ecological citizenship awareness among the community in Indonesia and to assess the impact of this awareness on community participation in environmental cleanliness and preservation programs. The method used is a literature study, which involves collecting and analysing related literature, including journal articles, research reports, and policy documents. The literature criteria applied include relevance, source reliability, and year of publication to ensure that the information obtained is accurate and up to date. The results of the study indicate that ecological citizenship awareness in Indonesia varies, with much of the literature emphasising the importance of environmental education in improving community understanding. The discussion also indicates that although awareness is high, implementation in real action is often hampered by a lack of support from facilities and policies. This study recommends strengthening environmental education programs and collaboration between the government and the community to create a cleaner, more sustainable environment.